Religious Moderation And National Politics: Siyasah Dusturiyyah's Analysis Of Policies To Strengthen Religious Moderation In Indonesia - Ngimadudin; Makarimal Akhlaq, Muftih; Anwar, Syaiful; Putra, Ifansyah (El-Ghiroh : Jurnal Studi Keislaman, 2026)
IIndonesia is a very pluralistic country in terms of religion, culture, and ethnicity, so a religious paradigm is needed that is able to maintain social harmony and prevent the emergence of extremism and intolerance. Religious moderation then became the state's strategic policy to maintain harmony, as emphasized through Presidential Regulation Number 58 of 2023. This article aims to analyze the policy of strengthening religious moderation from the perspective of siyasah dusturiyyah, which is a branch of fiqh siyasah that discusses the constitution, justice, and public benefit in the Islamic political tradition. This study uses a literature review method with a qualitative-descriptive approach through analysis of religious moderation literature, national politics, and fundamental concepts in siyasah dusturiyyah and the rules of fiqh siyasah. The results of the discussion show that religious moderation as a state policy is in line with the basic principles of siyasah dusturiyyah, such as justice (al-'adalah), equality (al-musawah), religious protection (hifz ad-din), public benefit (al-maslahah al-'ammah), and prevention of damage (dar' al-mafasid). State policies in strengthening religious moderation also meet the rules of fiqh such as tasarruf al-imam manuthun bi al-maslahah and al-'adah muhakkamah, so that they have normative legitimacy from an Islamic perspective. However, the implementation of religious moderation still faces structural, cultural, and interpretive challenges, especially related to inter-institutional coordination, resistance from extreme groups, and concerns about policy politicization. Overall, religious moderation is a harmonious combination of Islamic values, national political needs, and Indonesia's constitutional framework in maintaining national harmony and resilience.